2014
DOI: 10.1055/s-0034-1390797
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of short period, low dose oral prednisolone for the prevention of stricture after circumferential endoscopic submucosal dissection (ESD) for esophageal cancer

Abstract: Background and aims: Endoscopic submucosal dissection (ESD) was developed in Japan and has been performed on many patients with early stage esophageal cancer; however quality of life in patients with postoperative stricture is drastically decreased and repeat, periodic endoscopic balloon dilatation (EBD) is usually required over long periods. In this study, we evaluate the efficacy of short period, low dose oral prednisolone in controlling post-procedural esophageal stricture. Patients and methods: In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 23 publications
6
70
0
Order By: Relevance
“…In this study, the oral steroid group showed a significantly lower stricture rate than the other two groups when the mucosal defect affected >75% of the circumference of the esophagus. This result is consistent with the results of other studies reporting the effectiveness of oral steroids in preventing post‐ESD strictures . In those studies, a stricture was defined as either the complaint of dysphagia or inability to pass an endoscope, or the inability to pass an endoscope with an outer diameter of 9.8 mm through the esophagus .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the oral steroid group showed a significantly lower stricture rate than the other two groups when the mucosal defect affected >75% of the circumference of the esophagus. This result is consistent with the results of other studies reporting the effectiveness of oral steroids in preventing post‐ESD strictures . In those studies, a stricture was defined as either the complaint of dysphagia or inability to pass an endoscope, or the inability to pass an endoscope with an outer diameter of 9.8 mm through the esophagus .…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with the results of other studies reporting the effectiveness of oral steroids in preventing post‐ESD strictures . In those studies, a stricture was defined as either the complaint of dysphagia or inability to pass an endoscope, or the inability to pass an endoscope with an outer diameter of 9.8 mm through the esophagus . Circumferential defects in patients included in those studies were complete circumferential ESD in some and >75% of the lumen in others .…”
Section: Discussionsupporting
confidence: 88%
“…In line with this, another report showed that the percentage of postoperative stricture after application of PGA sheets was 7.7% in patients with a mucosal defect covering greater than seven-twelfths of the esophageal circumference [14] . Furthermore, Kataoka et al [15] reported a case in which esophageal stricture was successfully prevented by endoscopic TA injection followed by the application of PGA sheets after a whole-circumferential resection. Therefore, it is important to consider alter- Representative case with esophageal stricture after ESD and TA injection.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of systemic (oral) steroids to decrease incidence of post‐ESD strictures was reported in three observational studies (Table ) . Although these small retrospective studies described no severe adverse events, long‐term systemic steroid therapy may cause adverse events.…”
Section: Management Of Adverse Events Related To Esophageal Esdmentioning
confidence: 99%